Manajemen Kurikulum Merdeka Belajar Dalam Menggali Kemampuan Literasi Siswa Di Mi Al-Islam Banjarharjo Salaman : Independent Learning Curriculum Management in Exploring Students' Literacy Skills at MI Al-Islam Banjarharjo Salaman - Nuriya Galuh Candra; Milna Wafirah; Laili Syarifah (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2023)
Literacy ability is a crucial indicator in assessing the quality of a country's education. Literacy encompasses reading, writing, critical thinking, and communication skills. This study aims to analyze the management of the Independent Learning Curriculum at MI Al-Islam Banjarharjo Salaman using the POAC (Planning, Organizing, Actuating, Controlling) approach to enhance students' literacy skills. The study employs a qualitative method, collecting data through interviews, observations, and documentation. Data were analyzed using content analysis to produce objective and systematic conclusions. Curriculum planning includes annual, semester, weekly, and daily programs. Organizing involves task allocation based on the Teacher Work Guidelines (BPKG). Curriculum implementation includes literacy activities such as 10-minute reading sessions and reading corners, while supervision is conducted through weekly and semester evaluations. The research subject is Mrs. Rodhiyah, S.Pd.I, the principal, along with teachers and students at MI Al-Islam Banjarharjo. The results show that the Independent Curriculum management enhances students' reading interest and literacy skills, despite challenges from limited facilities.